Overcoming English Speaking Challenges: A Role-Playing Simulation Approach in Vocational Education - Madjid, Merla (Journal La Edusci, 2025)
The ability to speak English is crucial in today's globalized era, especially for vocational students in agro-industrial engineering. However, traditional teaching methods often fail to develop speaking skills effectively, leading to low confidence and motivation among students. Constructivist theories emphasize active student involvement and real-life simulations as effective learning approaches. This study aimed to evaluate the effectiveness of the role-playing simulation method in improving the English-speaking skills of Agro-Industrial Engineering students at Politeknik ATI Makassar. A quasi-experimental research design with a mixed-method approach was employed. The participants were 30 second-semester students. Data were collected through speaking tests (Test 1, Test 2, Test 3), observation sheets, and interviews. Quantitative data were analyzed using descriptive statistics and Cohen's d for effect size. The research involved six meetings with various business communication scenarios. The average speaking test scores significantly increased from 66.67 (Test 1) to 75.03 (Test 2) and 81.27 (Test 3). Cohen's d values indicated a medium effect for Test 1 vs Test 2 (d=0.72) and Test 2 vs Test 3 (d=0.61), and a large effect for Test 1 vs Test 3 (d=1.29). Students showed increased confidence, motivation, and active participation, with more intelligent students assisting their peers. The role-playing simulation method significantly improved English-speaking skills, confidence, and motivation among agro-industrial engineering students. This method provides a practical and effective alternative to conventional teaching, aligning with constructivist learning principles and preparing students for industry needs. Future research should explore this method in different contexts with larger sample sizes